Data driven treatment response assessment and preterm, perinatal, and paediatric image analysis : first International Workshop, DATRA 2018 and third International Workshop, PIPPI 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16, 2018, Proceedings /: first International Workshop, DATRA 2018 and third International Workshop, PIPPI 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16, 2018, Proceedings. (2018) - Unknown
No abstract available